KAJIAN MODEL RASCH PADA TES LO DAN DESAIN DIDAKTIS PEMBELAJARAN ETNOMATEMATIKA SUNDA MELALUI PERMAINAN ENGKLEKMATIKA DALAM KEMAMPUAN PEMODELAN MATEMATIK KELAS III SD - Munawaroh, Siti; Supriadi, Supriadi (Universitas Pendidikan Indonesia Kampus Serang, 2021)
This study describes the success of a process of transferring knowledge from sources of knowledge to students through educators who are not just given it for granted. There needs to be something that can help the process of transfer of knowledge become more interesting so that students are interested and can receive new knowledge well, one of which is learning design. Ethnomathematics can be a new option for interesting learning designs for children. With this design choice, there is hope that children can develop their mathematical modeling skills. Modeling skills can help children make mathematical models in real life. Currently, there are still many educators who still do not know and use this ethnomathematical design option in classroom learning. In this study, we will discuss the results of the analysis of the LO, DDA, and RDD test measuring instruments for ethnomathematical learning with the Engklek game obtained from Supriadi's research data (2019). The method in this research is descriptive. Using this method will describe the results of the analysis of the Winstep application in the form of numbers in words that are easier to understand. The findings from the data that have been processed according to the items, namely, a test measuring instruments in the form of LO, DDA, and RDD can be used to measure students' mathematical modeling abilities because most of the analysis results show that they have met the analysis criteria. In LO 1 and LO 2 there are still some items that do not meet the criteria, so they cannot be used optimally to measure their mathematical modeling abilities. While in DD and RDD all items have met the criteria to be used as a measuring tool for the test.